You need to notice that the common ratio of the given geomteric sequence is `-1/2` and you may evaluate such that:

`(-1/4)/(1/2) = (1/8)/(-1/4) = -(1/16)/(1/8) = ... = -1/2 = r`

You should use the following formula for summation of `n` terms of geometric sequence, such that:

`S_n = (1/2)*(1 - (-1/2)^n)/(1 - (-1/2))`

`S_n = (1/2)*(1 - (-1/2)^n)/(3/2)`

`S_n = (1/3)*(1 - (-1/2)^n)`

Since the number of terms is infinite, hence `n -> oo` yields:

`lim_(n->oo) S_n = lim_(n->oo) (1/3)*(1 - (-1/2)^n)`

`lim_(n->oo) S_n = (1/3)*(1 - lim_(n->oo) (-1/2)^n)`

`lim_(n->oo) S_n = (1/3)*(1 +- 0)`

`lim_(n->oo) S_n = (1/3)`

**Hence, evaluating requested sum of the given infinite geometric seqeunce, yields **`lim_(n->oo) S_n = (1/3).`

**Further Reading**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now